XR programmers give their perspective on how XR technology can be effectively utilized in high-performance sport. - Le Noury, P. J.; Polman, R. C.; Maloney, M. A. (Sports Medicine - Open, 2023)
Background The successful use of extended reality (XR) in sport is highly dependent on the extent to which it can represent the perception-action couplings that exist in the performance setting. However, there are many unknowns regarding the effectiveness of XR technology which is limiting its adoption in sport. Therefore, providing high-performance sporting organisations with more information about the efficacy and utility of XR, specifically its strengths and limitations, is warranted.